Instructional Material Development for Modular Learning: Voices from Inexperienced English Language Teachers - Honey Thane A. Alban; Ericson O. Alieto (Future Science, 2022)
The spread of the Coronavirus pandemic had affected every sector in our community including the sector of education. Educational institutions all over the world were forced to temporarily close. The COVID-19 pandemic is continuously arising yet learners should continue to learn. Thus, the Department of Education together with other educational institutions in the Philippines decided to devise a learning continuity plan. The authorities and the stakeholders decided to utilize distance learning as an alternative to face-to-face classes. Specifically, public elementary and secondary schools used distance modular learning. The modules used in modular distance learning. Hence, this qualitative research study utilized the thematic analysis method to unveil the challenges and coping mechanisms of English language teachers in developing the modules. This study primarily aimed to present the challenges encountered by inexperienced English language teachers in developing the materials for the modular learning of English. Moreover, the coping mechanisms of the English language teachers against the challenges they faced while developing the modules are discussed herein.